In Vitro Effectiveness Test of Sagoo Cortex Liquid Smoke to Inhibit the Growth of Ganoderma orbiforme (Fr.) Ryvarden - M Yusmar; Antama Surwadinata; Irwan Tasla; Oksana Oksana; Syukria Ikhsan Zam (Jurnal Penelitian Pendidikan IPA, 2022)
Ganoderma orbiforme is a pathogenic fungus that cause basal stem rot especially in oil palm, so it needs to be controlled. One of the alternative controls used is liquid smoke. This research aims to examine several concentrations of sagoo cortex liquid smoke to inhibit the growth of G. orbiforme in vitro. This research was conducted in October untill Desember 2021 at the Pathology, Entomology, Microbiology and Soil Science Laboratory, Faculty of Agriculture and Animal Science, Islamic State University Sultan Syarif Kasim Riau. Research was test of 6 concentrations of sagoo cortex liquid smoke (0, 1, 2, 3, 4, and 5%) with 4 replications. Liquid smoke had a total phenol Â± 7.44%. Sagoo cortex liquid smoke with 1% concentration has already very effective to inhibit in the macroscopic, microscopic, growth rate, wet mass and dry mass